LIRIK LAGU SEMUA AKU DIRAYAKAN KARYA NADIN HAMIZAH - Gusnatul, Laila (UNIVERSITAS PGRI YOGYAKARTA, 2024)
Songs are literary works that express certain meanings through the words placed in the text. The meaning of a song is explained by its lyrics, which can also express the author's feelings or opinions about something. The aim of this research is to analyze the lyrics of Nadine Hamizah's song